FACTORS RELATED TO THE INCIDENCE OF DIARRHEA IN TODDLERS (1-4 YEARS) IN PUJA MULYA VILLAGE, BANDAR DISTRICT, BENER MERIAH REGENCY - Yusafrita, Yusafrita; Fahdhienie, Farrah; Raiyan, Deka (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2025)
Background: Diarrheal disease frequently causes outbreaks (KLB) with a large number of cases occurring in a short period. It remains a leading cause of mortality among children under five in Indonesia. The primary cause of death due to diarrhea is inappropriate management, both at the household level and in healthcare facilities. Reducing mortality from diarrhea requires prompt and proper treatment. Method: This research is a descriptive-analytic study with a cross-sectional design, using interviews for data collection. The population studied was from January to June 2019, with a total sample size of 80 individuals, representing the entire population. Data collection was conducted from July 25 to August 8, 2019. Data were analyzed using univariate and bivariate analysis with the non-parametric Chi-square test. Result: Univariate analysis showed that 24 children (30%) had diarrhea, while 56 (70%) did not. Regarding knowledge, 36.3% of respondents had high knowledge and 63.8% had low knowledge. For exclusive breastfeeding, 30% had been given exclusively and 70% had not. As for Clean and Healthy Living Behavior (PHBS), 40% practiced it well and 60% did not. Bivariate analysis indicated no significant relationship between knowledge and diarrhea incidence (p-value = 0.312), a significant relationship with exclusive breastfeeding (p-value = 0.016), and no relationship with PHBS (p-value = 0.808) at a significance level of α = 0.05. Recommendation: Parents are advised to pay greater attention to the health conditions of children with diarrhea, particularly in ensuring exclusive breastfeeding and applying proper Clean and Healthy Living Behaviors. Preventive measures should be taken before symptoms appear, and immediate consultation with a doctor is recommended when diarrhea symptoms arise in toddlers.